Connecting with the Ivory Tower : Business Perspectives on Knowledge Exchange in the UK /: Business Perspectives on Knowledge Exchange in the UK. ([2013]) - (Professor emeritus of enterprise studies), Hughes, Alan; Kitson, Michael, 1959-
No abstract available